2020
DOI: 10.3390/ph13090259
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of Non-Selective Small Molecule Antagonists of the Bradykinin Receptors

Abstract: Angiotensin converting enzyme 2 (ACE2) downregulation is a key negative factor for the severity of lung edema and acute lung failure observed in patients infected with SARS-CoV-2. ACE2 downregulation affects the levels of diverse peptide mediators of the renin-agiotensin-aldestosterone and kallikrein-kinin systems, compromising vascular hemostasis. Increasing evidence suggests that the inflammatory response observed in covid-19 patients is initiated by the action of kinins on the bradykinin receptors. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This screening confirms previous reports demonstrating anti-SARS-CoV-2 activity of hydroxychloroquine, amlodipine besylate, arbidol hydrochloride, tilorone 2HCl, dronedarone hydrochloride, mefloquine, celecoxib, and thioridazine hydrochloride (8)(9)(10)(25)(26)(27), while identifying additional 12 drugs. However, there are seven drugs have been reported when our manuscript was underreview (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The underlying mechanisms of viral replication inhibition by these drugs are not clear.…”
Section: Discussionmentioning
confidence: 96%
“…This screening confirms previous reports demonstrating anti-SARS-CoV-2 activity of hydroxychloroquine, amlodipine besylate, arbidol hydrochloride, tilorone 2HCl, dronedarone hydrochloride, mefloquine, celecoxib, and thioridazine hydrochloride (8)(9)(10)(25)(26)(27), while identifying additional 12 drugs. However, there are seven drugs have been reported when our manuscript was underreview (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The underlying mechanisms of viral replication inhibition by these drugs are not clear.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, the use of bradykinin antagonists is supposed to be regarded as a strategy for COVID-19 treatment interventions. Currently, only icatibant has been approved as bradykinin antagonist for clinical treatment, and relevant studies have revealed that cefepime, cefpirome, imatinib, raloxifene, sildenafil, ponatinib, abemaciclib and entrectinib may also act as prospective non-selective bradykinin antagonists and have potential for treatment of COVID-19 ( Rasaeifar et al, 2020 ). However, further researches into the mode of action, efficacy and safety of these drugs are required.…”
Section: Putative Drug Targets For Pulmonary Edema In Covid-19 Patientsmentioning
confidence: 99%
“…Vitual screening on the DrugBank [ 23 ] was carried out using the Molecular Operating Environment (MOE) program [ 28 ], using four common points of the BK B1 and B2 pharmacophores described previously [ 25 , 26 ] that were used as a query. Previously, a 3D DrugBank database containing the 3D structure, together with a set of conformations of each molecule, was constructed as explained elsewhere [ 24 ]. Virtual screening was carried out on the subset of molecules with molecular weight between 200 and 600 (a total of 1703 molecules).…”
Section: Methodsmentioning
confidence: 99%
“…In other to swiftly test the efficacy of alternative BK antagonists with diverse pharmacological profiles for the treatment of Covid-19, drug repurposing represents a valuable strategy [ 22 ]. To this aim, we recently carried out a virtual screening study on the DrugBank database [ 23 ] aimed at identifying BK ligands among drugs already approved by the FDA [ 24 ]. The study was carried out using four points common to the pharmacophores derived for the B1 and B2 bradykinin receptors recently reported that were used as queries for the search [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation